Contrastes y desigualdades entre zonas turísticas y vecinales en el puerto de Ensenada, Baja California - Laura Susana Zamudio Vega; Roberto Goycoolea Prado (Études Caribéennes)
The Ensenada port in Baja California is one of the main tourist destinations in northwest Mexico. Its proximity to the United States favours the visitors’ reception, who hold an important part of its economy. The tourist awakening of the so-called Pacific Cinderella arose from an unforeseen event: the enactment in the nearby country of the Dry Law (1920), which prohibited the manufacture, import, sale and consumption of alcoholic beverages. Thousands of Americans found in northern Mexico a place to avoid the prohibitions. Tourism development was explosive.Over the years, tourism in Ensenada has been consolidated and diversified, including from family tourism on the coast to enotourism in Guadalupe Valley. However, one of the biggest - if not the main - tourist draw of the city continues to be alcohol consumption and the associated adult entertainment activities. What is new is the growth of cruise tourism, which has conditioned the port and the historic centre development, generating a shared, but at the same time disputed, space with the neighbors. Space where diverse conflicts are manifested emphasized by the marked social and spatial inequalities existing between and non-tourist areas.In this context, this paper presents the results of a research project where, among other topics, study the perception of the problems generated by cruise tourism in the uses and customs of Ensenada historic center. We were particularly interested in the conflicts generated by the real and symbolic use of space and the sensation of urban polarization marked by tourism in morphology, mobility and urban image. The limited impact on space and time of cruise tourism in Ensenada allows us to generalize -as a warning, we understand- the analysis of the benefits and problems detected.